The possibilities of repertory grid technique as a method of research of the self-system - Kujalienė, Dalia (Psichologija, 2004)
Self is a topic of great interest and very widely researched problem in psychology. Nevertheless after a century of researches and discussions there is no theory and definition of the self which would agree most of scholars with. Very viable is distinction between two fundamental aspects of the self, the “I” and the “Me”, self as a subject and self as an object. I-self is the knower, the active agent responsible for constructing of the Me-self. “I” initiates and controls activity, processes information about self. “Me” represents all things known about self. “Me” came to be labeled the self-concept and has received major attention of researchers. There are many definitions of the selfconcept. Discussions about its nature, structure and influence on the functioning of a person are still continuing. One can find very little agreement in consideration of these questions. It is possible to trace out three common themes that almost all scholars recognize: knowledge about the self, evaluation of self and feelings towards self. Because of theoretical confusion there is no satisfactory method of research of self-concept. Various theoretical models of the selfconcept are in essence sets of dimensions which are invented by authors. Researches using the methods, based on these models, almost always confirm theoretical presumptions. The question arises: are these dimensions really those which exhaustively reveal true content and structure of self-concept? Some authors question the purposefulness of nomotethic investigation in this area and suggest to change the point of view to the problem from researcher’s perspective to the perspective of participants, and apply ideographic, phenomenological methods for the research of self.One of the method of the investigation of self, poorly known in Lithuania, is repertory grid technique based on G. A. Kelly’s personal construct theory.From the standpoint of personal construct theory self can be treated in three ways: 1) as an object (element) that can be evaluated by some dimensions, 2) as construct “Me – not-Me” (construct is a dimensijon used by the person for interpreting of himself and surrounding world), other objects can be evaluated as “like Me” and “not like Me”; 3) as a system of constructs – self-system, the sum of constructs related with the pole “Me” of construct “Me – not-Me”. Selfsystem is the central part of personal construct system and influences all its functioning. As every construct system self-system is just one of possible ways of interpreting of self and thus it may be not accurate and adequate. The main function of self-system is to help the person to predict his reactions to future events and to control his needs, emotions and actions.Repertory grid technique allows to reveal unique individual content, structure and evaluative aspects of the self-system and thus shows person’s view to himself from his own perspective. In order to investigate the self-system two schemes may be used. First, when various aspects of the self (Me as I am, as I would like to be, as I ought to be, etc.) are used as elements. Second, when various aspects of the self are used as constructs. In this case other people important to the person under investigation are used as elements. The content of self-system can be revealed through constructs that are related to different aspects of the self. The structure of self-system can be find out, analisying relationships of constructs. The evaluative aspect of self-system becomes clear from the relationship between real and ideal self.The aim of this paper is to demonstrate the possibilities of repertory grid technique as a method of research of the self-system by presenting three individual cases. The rating grid was used. The scheme of investigation: 1. filling in of the list of elements; 2. construct elicitation using dyads of elements; one of elements always was “Me as I am”; 3. rating of elements on each construct on 5 point scale. The result of this process – an element by construct matrix of ratings that could be analysed by various methods of mathematical statistic. Correlation analysis was performed. Intensity and relation scores were computed. The graphical representation of self-systems was presented.Three given cases represent very different content and structure of the self-system and self-evaluation of participants. Each participant used different set of constructs for self-interpretation. Three types of the structure of self-system were revealed: monolithic, integrated and diffuse. Through the correlation between real and ideal self the level of self-evaluation emerged. One common feature of participants was detected – the importance of “ought self”. Results help to understand the personal problems that participants can face with.
Keywords: repertory grid technique; self system